CONSERVATION AND ARCHIVING MEDICAL RECORDS IN SELECTED HOSPITALS IN YAOUNDÉ - Agbor, Dr. Michael Ashu; C, Tchweguem; S, Zing; L.P, Fonkoueng Nguichou; Che B, Ndikum; Nchifor A, Menguih; P, Lindondo (International Journal of Research -GRANTHAALAYAH, 2024)
Introduction: Medical records play an important role in the storage and recall of patient’s information, patient’s follow-up, research, teaching, public health policy making and as a medico-legal tool, but less emphasis has been placed on its role in health care delivery. The objective of the study was to appraise the methods of conservation and archiving of medical records in hospitals in the city of Yaoundé. Methodology: A descriptive cross-sectional study was done in the hospitals of Yaoundé between January to June 2023. The Data which was collected from medical record clerks using a self-administered and pre-tested questionnaire included: The profile of the health institution, personal information of the clerks, strategies put in place for the protection of medical records and obstacles in archiving. Results: Twenty hospitals in the city of Yaoundé participated in the study. The public sector represented 65% of the health facilities, 45% had been existing between 21 and 40 years, with a median of 24.5 years. In 70% of the cases, medical records archiving system had been existing between 1 and 10years. In 65% of cases, the conservation of archived records was mainly done at the different services with the paediatric service being the most represented (16.2%). In 87.5% of cases, the means of archiving used was the paper file classified on shelves (73.5%); of which (52.2%) were archived in alphabetical order. The obstacles to archiving medical records were mainly the lack of qualified personnel (82.4%) and the lack of storage space (80.1%). Conclusion: Many obstacles were observed. These results suggest actions to be generated both by the Cameroonian State and by the leaders of private health facilities in order to improve the management of medical records.